KUALITAS VISUM ET REPERTUM PERLUKAAN DI RSUD PURI HUSADA TEMBILAHAN PERIODE 1 JANUARI 2009-31 DESEMBER 2013 - Hirfawaty, Hetty; Afandi, Dedi; Chandra, Fifia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTThe most frequent Visum et repertum (VeR) requested by investigators is VeR of injury. This study was aimed to understand the quality of VeR of injury in Tembilahan Puri Husada General Hospital during 1 January 2009-31 December 2013. The research was an observational study using descriptive retrospective design. This study used Herkutanto’s scoring method towards 13 VeR substances. Samples of this study were all data of VeR of injury. It had been gotten 325 VeR reports in Tembilahan Puri Husada General Hospital during 1 January 2009-31 December 2013. Injury survivors most cases are in the age group 22-40 years old as many as 174 victims (53,54%). The overview of the living victims were most frequent male was 221 victims (68%) and the most frequent violence that were experienced by the victims were blunt violence was 253 VeR (77,85%) with the highest age group 22-40 years old. About 80% showed good quality in preliminary unit of VeR, 39% showed poor quality in reporting unit and about 49% also showed poor quality in inference unit. It can be concluded that quality of VeR reports in Tembilahan Puri Husada General Hospital during 1 January 2009-31 December 2013 was 47,67% which was mean it was poor quality.Keywords: Visum et Repertum, injury, quality of VeR of injury